Fine needle aspiration cytology of breast lesions: Diagnostic values - Al-Rubai’ee, Nada S.; Al-Rubai’ee, Nada S. (Journal of the Faculty of Medicine Baghdad, 2007)
Back ground:Fine needle aspiration (FNA) is indicated in the exploration of superficial and deep masses. The accuracy of this procedure differs in various studies, and according to the organ explored. Palpable mammary masses of concern to the patient or clinician should be aspirated, regardless of imaging findings. Objective: The present study aimed at evaluation of cytological results of FNA of different palpable breast lesions, using histopathological diagnosis as the gold standard for final diagnosis. Patients & Methods: This prospective study includes 289 females with palpable breast lesions. FNA aspiration was conducted in a private out patient clinic during the period of 1994-2004. The cytological results of aspirated masses are compared with the histopathological result of biopsies or surgical specimens. Estimation and evaluation of the validity parameters of cytology and histopathology were performed. Results: Out of seventy one (71)cases of malignant neoplasms diagnosed in histopathological; sixty three (63) showed malignant cellular aspirates, four (4) showed atypical cellular changes and four (4) were negative for significant cellular findings on FNA. On the other hand out of (217) benign lesions diagnosed by histopathology; 15 showed atypical epithelial changes on cytological aspirates while the rest showed benign cellular aspirates. Twenty (20) cases out of the whole sample showed epithelial cellular atypia on FNA; four of them proved to be malignant, one case revelead atypical epithelial hyperplasia or epithelioisis, and the other 15 proved to be benign lesions by histopathology. The validity parameters of FNA were as follows; sensitivity= 88.7%, specificity= 100%, False negative results= 11.3% and accuracy= 96.1%. Conclusion: F. N. A. is a quick, inexpensive, relatively painless safe procedure from which results can be obtained in a short time with the other supportive investigations. Adequacy determination must be based not only on the cytological findings but also on their correlation with the clinical, mamrnographic, and ultrasonic findings to avoid false negative results. Atypical epithelial changes on cytological smears indicate the need for immediate excional biopsy.